Transitions of Self: Assuming or Leaving a Chair Role - Denise Bullock (Academic Chairpersons Conference Proceedings, 2023)
We experience multiple transitions throughout our lives. Transitioning from faculty to chair is one of those key transitional moments in which our sense of self shifts with the change in role. Participants will work through a series of exercises to discover, analyze, and plan for that transition of self.
Keywords: self; transition; identity; self-reflection; trajectory; workshop